Land use as a major factor of riverine nitrate in a semi-arid farming-pastoral ecotone: New insights from multiple environmental tracers and molecular signatures of DOM - Li, Cai; Yue, Fu-Jun; Li, Si-Liang; Ge, Jin-Feng; Chen, Sai-Nan; Qi, Yulin (Frontiers in Environmental Science, 2022)
The nitrogen contamination in rivers has become significant concern in arid and semiarid areas due to water resource shortage and extensive anthropogenic activities in relation to land-use changes in China. As a major nitrogen species, identifying driving factors, transformation and sources of nitrate is crucial for managing nitrogen pollution in rivers. In this study, nitrate sources and transformations were deciphered using physicochemical variables, molecular signature of dissolved organic matter and coupled isotopes of nitrate under different land use types in the Yang River, a typical farming-pastoral ecotone in the semi-arid area of North China. The results of river water showed a significant positive correlation between NO3− concentrations, δ15N-NO3− values and percentage of urban land and cropland, which confirmed the critical role of land use in the variations of riverine nitrate. The correlation between DOM composition (aliphatic and lignin-like compounds) and NO3−/Cl− ratios as well as Cl− concentrations verified the effect of agricultural activities on nitrate source and transport. The variation in water chemical variables and dual isotopes of nitrate in river and soil extracts (δ15N-NO3− and δ18O-NO3−) was indicative of the concurrence of in-soil nitrification process and assimilation, whereas denitrification was inhibited under aerobic conditions in the semiarid area. The Bayesian model revealed that about 60% of nitrate was derived from non-point sources (manure, SON and CF) and 36% from sewage. Although urban is not the major land-use type in the farming-pastoral ecotone, sewage contributed to about 36% of nitrate. The source identification of nitrate stresses the importance of the management of non-point pollution and demand for sewage treatment facilities in the farming-pastoral ecotone. This multiple-tracer approach will help gain deeper insights into nitrogen management in semi-arid areas with extensive human disturbance.